Prognostic Factors Influencing Outcome in Patients with Spinal Cord Injury - Nafeesuddin; Khan, Zahid; Ali, Sardar; Muhammad Saqib; Ijaz ul Haque; Khan, Naveed (Indus Journal of Bioscience Research, 2025)
Background: Spinal cord injury is a devastating neurological condition resulting in permanent motor, sensory, and autonomic deficits. Traumatic and non-traumatic mechanisms lead to primary neural disruption, followed by secondary pathophysiological cascades such as ischemia, inflammation, and excitotoxicity, which exacerbate tissue damage. Prognosis is influenced by injury level, completeness, mechanism, timing of intervention, and associated complications, yet local data on determinants of adverse outcomes are limited. Objective: To determine the frequency of factors leading to adverse outcomes in patients with spinal cord injury. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from February to May 2025 at the Department of Neurosurgery, Lady Reading Hospital, Peshawar. Methodology: A total of 113 patients aged 18–50 years, presenting within 14 days of spinal cord injury, were enrolled through consecutive sampling. Neurological assessment using the American Spinal Injury Association Impairment Scale and magnetic resonance imaging confirmed spinal cord injury. Factors analyzed included cervical and thoracic injury, incomplete motor function, traumatic etiology, surgical management, and spasticity. Results: Participants were predominantly male (71.7%), with a mean age of 36.6 years and body mass index of 26.3 kg/m². Cervical injuries were most frequent (80.5%), thoracic injuries were less common (9.7%), and 35.4% were classified as having incomplete motor function. Traumatic causes were identified in 69.9% of patients, 44.2% underwent surgery, and 77.9% exhibited spasticity. Conclusion: Adverse outcomes in spinal cord injury are influenced by demographic, socioeconomic, and clinical factors.